The Legitimacy of Papacy - Fernandez, Jose (2015)
Since he became pope, Jorge Mario Bergoglio seems to have started a new era in the Vatican. As is usually said, he is the first Jesuit and the first South American in history to govern the Catholic Church. Francis, as it will be argued here, raises many interesting questions to political theory. His figure is now globally accepted in a world where politicians lack of popularity or loose it very soon. ¿Will he solve the deep legitimation crisis of the Church he received? Besides, his critics from within and fro outside the Church, accused him of being a populist. They say he comes from a country with a deep inclination to populism. ¿How much has Argentine political culture, and recent history, influenced Francis?s political strategy? Francis has also changed the bulk of the Church discourse towards society, insisting in subjects like social inequality, motivating priests to go with joy where the people are an denouncing the tragedies of migrants as well as the sadness and solitude of those living in contemporary world, even if they are not poor. This article will address those topics and offer an answer to the theoretical questions they pose. "The Legitimacy of the Papacy", Politics and Religion (Belgrado) Center for Study of Religion and Religious Tolerance, Vol. IX, Nº 1, Primavera de 2015, pp. 85-108. ISSN 1820 6581; ISSN 1820 659X (on-line). politicsandreligionjournal.com/images/pdf_files/engleski/volume9_no1/vega.pdf http://politicsandreligionjournal.com/index.php?option=com_content&view=category&layout=blog&id=6&Itemid=3&lang=en